The Era of Uncertainty and Ethical Arrangement in Javanese Classical Texts: Disseminating Ranggawarsita’s Works as Source of Islamic Ethics in Islamic Higher Education - Zumrotul Mukaffa (Al-Jami'ah: Journal of Islamic Studies, 2018)
This paper investigates the era of uncertainty and ethical arrangement formulated in the Javanese classical text written by Ranggawarsita. Most of his works, especially Serat Kalatidha, Serat Sabdapranawa, and Serat Sabdatama, situated in the era of uncertainty and moved to the era of zaman edan (crazy age), kalabendhu (age of anger), owah or pakewuh (bizar time). Social structure in this era tied to unethical behavior. Elite communities were lacking of self- representation as a good example, meanwhile the communities were ignoring public advisability.  To set free from uncertainty condition is possible through implementing four ethical doctrines in the social life, namely: Monotheistic behavior, active submission to God’s predestination, self-contemplation, and eling lan waspada (self-awareness and mindfulness). The dynamic of nationhood today is almost reflecting the age of kalabendhu, and therefore it is necessary to do dissemination and transformation of ethical doctrines in the Islamic Higher Education by using the doctrine as a source of subject of Islamic Ethic. The need of dissemination is because academia in the Islamic Higher Education is an integral part of uncertain social structure.